Exergy analysis of a flat plate solar collector with latent heat storage by phase change material for water heating applications at low temperature - Angie Rincon Ortega; Mauricio Carmona (Alanya Hamdullah Emin Paşa Üniversitesi, 2017)
An exergy analysis has been performed to determine the potential for useful work in a latent heat storage system with phase change material (PCM) for a flat-plate solar collector. Commercial paraffin wax is used as PCM to store and release energy in the solid-liquid transformation; this material is located in metal containers under the absorber plate on the bottom insulation of the collector. The exergy analysis is performed in outdoor conditions for days of the low, medium and high radiation taken from October 2016 to March 2017 at Barranquilla city (latitude: 10º 59' 16